2017
DOI: 10.1111/jvim.14793
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Respiratory Cycle on Caudal Vena Cava Diameter Measured by Sonography in Healthy Foals: A Pilot Study

Abstract: BackgroundIntravascular volume assessment in foals is challenging. In humans, intravascular volume status is estimated by the caudal vena cava (CVC) collapsibility index (CVC‐CI) defined as (CVC diameter at maximum expiration [CVC max] – CVC diameter at minimal inspiration [CVC min])/CVC max × 100%.Hypothesis/ObjectivesTo determine whether the CVC could be sonographically measured in healthy foals, determine differences in CVC max and CVC min, and calculate inter‐ and intrarater variability between 2 examiners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 32 publications
2
18
1
Order By: Relevance
“…Bodyweight was measured at baseline and 6 h. Packed cell volume (PCV), total solids (TS), albumin, electrolytes, lactate, urine specific gravity, vital parameters, gastrointestinal borborygmi and central venous pressure were measured every 2 h. Results: Rectal fluid administration with plain water was well tolerated and caused clinical chemistry changes consistent with haemodilution, indicating absorption. Mean (95% confidence interval) PCV decreased from 40% [40][41][42] at 0 h to 35% [34][35][36] at 6 h during rectal fluid treatment (P<0.001), similar to decreases in PCV occurring also with i.v. and nasogastric (NGT) treatment (P<0.001).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…Bodyweight was measured at baseline and 6 h. Packed cell volume (PCV), total solids (TS), albumin, electrolytes, lactate, urine specific gravity, vital parameters, gastrointestinal borborygmi and central venous pressure were measured every 2 h. Results: Rectal fluid administration with plain water was well tolerated and caused clinical chemistry changes consistent with haemodilution, indicating absorption. Mean (95% confidence interval) PCV decreased from 40% [40][41][42] at 0 h to 35% [34][35][36] at 6 h during rectal fluid treatment (P<0.001), similar to decreases in PCV occurring also with i.v. and nasogastric (NGT) treatment (P<0.001).…”
mentioning
confidence: 58%
“…In humans, CVP shows a poor correlation to blood volume as evidenced by a systematic review and meta-analysis and is now not recommended to be used to guide fluid therapy [38,39]. Noninvasive techniques, such as inferior vena cava collapsibility index (IVC-CI), are emerging in humans and the utility of a similar technique has been demonstrated in foals (caudal vena cava collapsibility index [CVC-CI]) [40][41][42]. These techniques, although promising, require further assessment in horses and may be useful for future studies [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…According to Tuplin et al (2017), in healthy standing foals CVC was easily and consistently obtained during sonographic measurement and the significant variation between CVC diameters in inspiration and in expiration allowed the calculation of the CI. Bucci et al (2017) investigated the ability of distensibility index of the caudal vena cava (CVCDI) to predict fluid response in healthy, anesthetized and mechanically ventilated dogs.…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, 2 studies reported a positive correlation between CVP and caudal vena cava diameter (CVC D ) in anesthetized dogs receiving IV fluids and positive pressure ventilation . Three recent studies evaluating CVC diameter, CVC collapsibility (CVC CI ), and the CVC to Ao ratio (CVC/Ao) showed promise in evaluation of intravascular volume status in dogs . Another study on healthy dogs undergoing general anesthesia and mechanical ventilation reported that the CVC CI is a reliable predictor of fluid responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Three recent studies evaluating CVC diameter, CVC collapsibility (CVC CI ), and the CVC to Ao ratio (CVC/Ao) showed promise in evaluation of intravascular volume status in dogs. [18][19][20] Another study on healthy dogs undergoing general anesthesia and mechanical ventilation 21 reported that the CVC CI is a reliable predictor of fluid responsiveness.…”
Section: Introductionmentioning
confidence: 99%